2016
DOI: 10.1111/1754-9485.12489
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal melanoma treated with stereotactic fractionated radiotherapy and prophylactic intravitreal bevacizumab: The Dunedin Hospital experience

Abstract: This study reaffirmed that SRT achieves very good local control and eye retention rates. PIB did not appear to reduce the radiation retinopathy rate in this study, and more studies are required especially Phase II and III trials to determine PIB efficacy in preventing RR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…4,5,31,33,42,51 As astutely observed by Stang et al, 28 we do recognize that the current estimated incidence is likely to be an underestimate of the true incidence as an increasing amount of UM cases are being detected earlier and are likely smaller and therefore amenable to treatment with eye-preserving therapies such as with plaque brachytherapy, stereotactic radiotherapy, and proton beam radiotherapy. Indeed, in data extrapolated from published 23,24 and unpublished local audits, we estimate that there is an additional 28% of UM cases that were treated by plaque brachytherapy and stereotactic radiotherapy, treatment modalities that did not receive a histologic diagnosis before treatment. Furthermore, it is not currently a standard practice in NZ to obtain a prognostic tumor sample for eye-preserving therapies to reduce the risk of tumor seeding.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,31,33,42,51 As astutely observed by Stang et al, 28 we do recognize that the current estimated incidence is likely to be an underestimate of the true incidence as an increasing amount of UM cases are being detected earlier and are likely smaller and therefore amenable to treatment with eye-preserving therapies such as with plaque brachytherapy, stereotactic radiotherapy, and proton beam radiotherapy. Indeed, in data extrapolated from published 23,24 and unpublished local audits, we estimate that there is an additional 28% of UM cases that were treated by plaque brachytherapy and stereotactic radiotherapy, treatment modalities that did not receive a histologic diagnosis before treatment. Furthermore, it is not currently a standard practice in NZ to obtain a prognostic tumor sample for eye-preserving therapies to reduce the risk of tumor seeding.…”
Section: Discussionmentioning
confidence: 99%
“…Dose reduction may be important for toxicity reduction in particle therapy as it is in brachytherapy, and a prospective randomized trial of lower-dose (50 Gy) versus standard dose (70 Gy) proton radiation for small-to-moderate sized uveal melanoma showed no differences in a 5-year local or systemic recurrence or visual acuity loss, suggesting lower dose may be acceptable moving forward (44). In the past decade or two, linear accelerator (LINAC) stereotactic RT (SRT), or SRS with either LINAC or gamma knife has been investigated for its potential as an alternative option to proton beam (46)(47)(48)(49)(50)(51)(52)(53). The initial experiences showed that SRT and SRS offer a noninvasive alternative to enucleation and brachytherapy in the management of uveal melanoma, with similar outcome to proton beam therapy (46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Definitive Rt For Ocular Melanomasmentioning
confidence: 99%
“…If this damage is left unrepaired, acute and chronic side effects are observed. Degree of the side effects occurring in the eye depends on the dose and energy of irradiation implemented and amount of the tissue exposed to irradiation (1–2–3).…”
mentioning
confidence: 99%
“…Bevacizumab, an antiangiogenic agent, is a recombinant humanized monoclonal antibody that specifically binds to human VEGF, neutralizing biological activity. Topical and subconjunctival BV is widely used and reported to be effective in retina and choroid diseases progressing with neovascularization, age-related exudative macular degeneration, macular edema due to obstruction of the central retinal vein, diabetic retinopathy, and macular edema resulting from uveitis (1, 345).…”
mentioning
confidence: 99%
See 1 more Smart Citation